REGULATION AND USER DEMAND IN ARCHITECTURAL DESIGN - Harsritanto, Bangun I I.R. (architecture department, Engineering faculty, Universitas Diponegoro, 2022)
Indonesia has released SIMBG to assist with the building permit and function assessment in Indonesia. The implementations vary based on the full online, half online, or fully offline. So what is the requirement of the building permit and function assessment already? Because design is creativity and society is dynamically changing. The reference must be something that legal and being accepted by the building owner, government, and designers, that couldn’t be more than the regulation itself.